Does Foreign Direct Investment Boost Agribusiness? A Systematic Literature Review with a Focus on Nepal - Joshi, Anoj; Devkota, Durga; Subedi, Kapil Deb; Rai Poudyal, Bimala (Journal of Agriculture and Forestry University, 2026)
Foreign Direct Investment (FDI) is an essential catalyst for transforming agribusiness in developing economies through capital injection, technological circulation, and enhanced market connectivity. Despite agriculture’s central role in Nepal’s economy, FDI inflows into the sector remain limited and inconsistent. This systematic review synthesizes evidence from studies published between 2000 and 2024 across databases such as ScienceDirect, Google Scholar, and JSTOR to examine how FDI influences agribusiness performance globally, with a special focus on Nepal. Following the PRISMA framework, a total of 26,010 records were initially identified, of which 19,991 were shortlisted after applying date and language filters, screening based on inclusion criteria and removal of irrelevant studies, and 35 studies were included in the final synthesis. Drawing upon Spillover Theory, Linkage Theory, and Dependency Theory, the review analyzes policy evolution, sectoral trends, and empirical experiences from countries including India, Vietnam, Bangladesh, and Mozambique. Findings indicate that while FDI can enhance productivity, strengthen value chains, and promote commercialization, its impact is highly dependent on regulatory clarity, institutional capacity, land governance, and the host country’s absorptive ability. In Nepal, policy bottlenecks, land-use restrictions, weak coordination among government units, and inadequate monitoring have constrained potential benefits. Significant evidence gaps remain, particularly regarding project-level outcomes, environmental implications, and long-term developmental effects. The review concludes that maximizing FDI’s contribution requires coherent policy reforms, enhanced institutional mechanisms, improved data systems, and targeted incentives for responsible and inclusive investment.